Benzodithiophene and Benzotrithiophene as π Cores for Two‐ and Three‐Blade Propeller‐Shaped Ferrocenyl‐Based Conjugated Systems. Issue 40 (26th October 2017) - Rossi, Serena; Bisello, Annalisa; Cardena, Roberta; Orian, Laura; Santi, Saverio
Abstract : The syntheses of linear and star‐shaped bis‐ and tris(ferrocenyl) derivatives of benzo[1, 2‐ b :4, 5‐ b′ ]dithiophene and benzo[1, 2‐ b :3, 4‐ b′ :5, 6‐ b′′ ]trithiophene are achieved through one‐pot CuI/TMEDA‐catalyzed (TMEDA = tetramethylethylenediamine) multiple annulations of bromoethynylbenzenes with sodium sulfide. In addition, the preparation of the parent benzotrithiophene in a good yield with a short reaction time is achieved through the threefold annulation of 1, 3, 5‐trifluoro‐2, 4, 6‐tris(trimethylsilyl)ethynylbenzene. The computed structural and electronic features of these ferrocenyl derivatives as well as their UV/Vis spectra and electrochemistry are discussed, and the results provide insights into the effect of the presence of three rather than two ferrocenyl units. To the best of our knowledge, 2, 5, 8‐tris(ferrocenyl)benzo[1, 2‐ b ;3, 4‐ b′ ;5, 6‐ b′′ ]trithiophene is the first organometallic complex containing benzotrithiophene. Abstract : Two‐ and three‐blade propeller‐shaped bis‐ and tris(ferrocenyl) derivatives of benzodithiophene and benzotrithiophene are synthesized through one‐pot multiple thioannulation reactions. The synthesis of the parent benzotrithiophene in a good yield with a short reaction time is also achieved. The presence of the third ferrocenyl moiety drastically changes the intensity of the UV/Vis absorptions.